If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 3x + -1) = 30 Reorder the terms: 2(-1 + x + 3x) = 30 Combine like terms: x + 3x = 4x 2(-1 + 4x) = 30 (-1 * 2 + 4x * 2) = 30 (-2 + 8x) = 30 Solving -2 + 8x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8x = 30 + 2 Combine like terms: -2 + 2 = 0 0 + 8x = 30 + 2 8x = 30 + 2 Combine like terms: 30 + 2 = 32 8x = 32 Divide each side by '8'. x = 4 Simplifying x = 4
| 9-18x-15=-52-126+10x | | 20d=100 | | 15xD=300 | | (5+8x)+(3x)=7 | | 10.32+k=-36.4 | | 5(3x-7)-3(x+3)-19x= | | -4c^2+4c-14=0 | | 3(x+4)=5x-18 | | 9x=15+8y | | 20.24=1.2x+8 | | f(8)=4x+1 | | f(8)=4x+1 | | (X+2.2)-(0.4x+3)=9 | | -4+6=-2r+4(r-3) | | 14=27+x | | 3=3-7(x+3) | | y=2+7(0.2121212121) | | a=-9+x+1y | | 2g+h=4 | | x+12=3x-7 | | 2d+4=10-5d | | 3(x+7)=25-(2-x) | | 11+10x=81 | | 17=r-9 | | 6-(v-4)=2(6v-3) | | 11+10x=81 | | 6-(v-4)=2(6v-3) | | 17=r-9 | | 7x+14y=13 | | 30=3x^2+1x | | 79=m+34 | | 4x-4=64 |